Killing in Self-Defence in Rabbinical Law - Börner-Klein, Dagmar (Jewish studies quarterly, 1997)
To explore various cases of causing a person's death it is necessary to turn to the Midrashim on the Pentateuch and to the halakhic discussions in Sanhédrin and Maccot of Mishnah, Tosefta and the Talmudim. The Responsa and the medieval codification of Jewish law contain further material. Another important source is Maimonides' Mishne Torah which contains the currently accepted rabbinical traditions; it is, therefore, a reliable source for the rabbinical practice of Jewish law. This paper considers different cases of killing a person. It focuses on those aspects of causing a person's death that the rabbis judged to be excusable: a) while performing a duty, b) as a defence against the transgression of the Law of the revealed Torah, c) in order to save the life of a human being and d) carrying out a death sentence. According to rabbinical law only a Sanhedrin of 23 members could impose the death sentence. Nevertheless, medieval texts report that even in the absence of a Sanhedrin Jewish judges in medieval Spain made use of their privilege of judging criminal law which included the death penalty. As Salomon ben Adret argued, they decided to judge according to state law and not according to rabbinical law.